2000
DOI: 10.1046/j.1460-9568.2000.00944.x
|View full text |Cite
|
Sign up to set email alerts
|

Retinal ganglion cells with NADPH‐diaphorase activity in the chick form a regular mosaic with a strong dorsoventral asymmetry that can be modelled by a minimal spacing rule

Abstract: We have identified a class of retinal ganglion cells in the chick retina that can be labelled by NADPH-diaphorase histochemistry. These cells have a remarkable topographic distribution, being restricted to the dorsal hemiretina, and form a highly regular mosaic, as revealed by the analysis of nearest neighbour distribution and Delaunay triangulation. Autocorrelation analysis of the mosaic of NADPH-diaphorase-positive retinal ganglion cells shows that the mosaic spatial organization could be generated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 47 publications
6
24
2
Order By: Relevance
“…without affecting the crosscorrelation curve~L 12 !. replicate several different retinal mosaics~Galli- Resta et al, 1997Resta et al, , 1999Cellerino et al, 2000;Raven et al, 2003!. In this model, cells are positioned serially into the mosaic at random, subject to the constraint that the distance to the nearest-neighboring cell is greater than some minimal distance, d min . However, there are two main differences between the two models.…”
Section: Modeling Considerationsmentioning
confidence: 99%
“…without affecting the crosscorrelation curve~L 12 !. replicate several different retinal mosaics~Galli- Resta et al, 1997Resta et al, , 1999Cellerino et al, 2000;Raven et al, 2003!. In this model, cells are positioned serially into the mosaic at random, subject to the constraint that the distance to the nearest-neighboring cell is greater than some minimal distance, d min . However, there are two main differences between the two models.…”
Section: Modeling Considerationsmentioning
confidence: 99%
“…Differential retinal expansion may then create the variation in cell density, and, through interstitial dendritic growth, the corresponding variation in dendritic field size to which density is inversely related (Lia et al, 1987;Wässle et al, 1989;Rodieck and Marshak, 1992;Scheibe et al, 1995;Cellerino et al, 2000). Alternatively, horizontal cells may interact with neighboring cells during development to produce the correlation between intercellular spacing and dendritic field size, whereas their cone afferents may stimulate the detailed formation of their dendritic morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike Cellerino et al (2000), we identified other asymmetrical somata in the dorsal GCL. These were consistently shown with Wilson et al…”
Section: Comparison With Previous Studies On Chicken Retinamentioning
confidence: 62%
“…These cells were also Brn3 -negative but, because of their much lighter staining and also because they clearly were not part of the very regular array of darkly staining cells, we presume them to be a different cell type. While Cellerino et al (2000) described the ventral retina as almost devoid of nitrergic cells in the GCL, we were able to see a variety of cells ranging from moderately to very faintly stained. Some cells were Brn3-negative and might belong to the same population as the lightly staining cells of the dorsal retina, but others were Brn3-positive, and therefore represent a third cell type in the GCL.…”
Section: Comparison With Previous Studies On Chicken Retinamentioning
confidence: 68%
See 1 more Smart Citation